Answer:
-7 - 3a = 1 – 4a
Step one: Add 4a to -3a
-7 + a = 1
Step two: Add 7 to 1
A = 8
You're done! A=8 for this problem!
Hopefully this helps! Feel free to mark brainliest!
Answer:
9/56 is your answer.
Step-by-step explanation:
[7+2(5 - 9)2]/[(4+1)2 - 3(22)=
[7+2(-4)2]/[(5)2-66]=
[7+2(-8)]/[10-66]=
(7+-16)/(-56)=
-9/-56=
9/56 is your answer.
Well x is an obtuse angle
but the angle e,f,g is an acute angle
Step-by-step explanation:
-4x - 28 = -4(x + 7) or 4(-x - 7)
Topic: Algebraic factorization
If you like to venture further, do check out my insta (learntionary) where I regularly post useful math tips! Thank you!